Proposed minimal panel of antibodies for cost-effectiveness and accuracy in acute leukemias immunophenotyping: Prospective study at a tertiary care center. Issue 6 (2nd July 2016) - Singh, Neha; Pati, Hara Prasad P.; Tyagi, Seema; Deka, Roopam; Sharma, Rahul; Saxena, Renu
Abstract : Introduction : Flowcytometry has an essential role in the diagnosis and classification of acute leukemias. However, there exists a great degree of inter-laboratory variability on issues like panel selection, antibody combinations, gating strategies, fluorochromes, and clonal selection. Aim : The primary aim of this study was to derive a minimal panel of antibodies and evaluate its diagnostic usefulness in acute leukemias by flowcytometry by using the detailed immune-phenotype of different lineage-specific or non-specific markers. Materials and methods : This prospective observational study involved 400 newly diagnosed cases of acute leukemias. Bone marrow aspirate samples were subjected to morphological evaluation, cytogenetics and flow cytometric immunophenotyping. Results : A minimal panel of eight antibodies comprising of CD45/CD34/CD19/MPO/cytoCD3/CD64/CD117/CD79a was derived by applying different permutations and combinations with a diagnostic yield of 97.5%. The minimal panel was further validated by testing in an independent cohort of patients with similar demographic characteristics, where it showed a high diagnostic yield of 98% in comparison with the screening panels proposed by other recently published studies. Conclusion : It may be concluded that the diagnostic performance of the eight antibody panel is better than most other panels used across the different laboratories in terms of yield, number of antibodies used and the scientific approach used to derive and validate the results and so henceforth may be applied in any setting with limited resources for better diagnostic accuracy.